Trends in COVID‐19 Risk‐Adjusted Mortality Rates. Issue 2 (23rd October 2020) - Horwitz, Leora I; Jones, Simon A; Cerfolio, Robert J; Francois, Fritz; Greco, Joseph; Rudy, Bret; Petrilli, Christopher M
Abstract : Early reports showed high mortality from coronavirus disease 2019 (COVID‐19). Mortality rates have recently been lower, raising hope that treatments have improved. However, patients are also now younger, with fewer comorbidities. We explored whether hospital mortality was associated with changing demographics at a 3‐hospital academic health system in New York. We examined in‐hospital mortality or discharge to hospice from March through August 2020, adjusted for demographic and clinical factors, including comorbidities, admission vital signs, and laboratory results. Among 5, 121 hospitalizations, adjusted mortality dropped from 25.6% (95% CI, 23.2‐28.1) in March to 7.6% (95% CI, 2.5‐17.8) in August. The standardized mortality ratio dropped from 1.26 (95% CI, 1.15‐1.39) in March to 0.38 (95% CI, 0.12‐0.88) in August, at which time the average probability of death (average marginal effect) was 18.2 percentage points lower than in March. Data from one health system suggest that mortality from COVID‐19 is decreasing even after accounting for patient characteristics. Abstract :